A distributed cognition perspective for collaboration and coordination: Artifact ecologies in design studies - Vasiliou, Christina (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2017)
A distributed cognition perspective for collaboration and coordination: Artifact ecologies in design studies user is spread across devices, across physical or digital spaces or in-between face-to face sessions, building up to the necessity to consider the collection of devices as a whole interactive space. The design of “micro-interactions” remains important, but there is a bigger issue we need to consider. How can interaction designers construct efficient artifact ecologies for collaborative activities? To this aim we need to acquire an in-depth understanding of the complex interactions and interdependencies between collaborators and information technologies. Through a multi-phase design approach, this dissertation focused on understanding within-group interactions during collaborative learning activities in an artifact ecology. This dissertation consists of four phases, three sequential phases to collect and analyse data, and one integration phase. The first phase explored the use of physical and digital tools in an HCI course and the role of an artifact ecology in supporting collaboration and coordination around design tasks. The second phase aimed to transfer and apply the DiCoT methodological framework into a classroom setting towards building an understanding of collaboration and coordination in terms of physical arrangements, communication channels and mediating artifacts. The third phase addressed the social and evolutionary aspects of the artifact ecology and proposed an expansion for two models of the DiCoT framework. Finally, the fourth phase integrated findings from previous phases to provide design implications on how to construct classroom artifact ecologies and to address how DiCoT can be used as a methodological toolkit in classroom artifact ecologies. The dissertation concludes with practical guidelines and implications for practitioners and researchers on designing technological tools and set ups for the support of collaborative design activities in classroom settings.
Keywords: Distributed cognition; Artifact ecology; Collaboration space; HCI education